Assessing Pre-service Teachers' Attitudes towards Research Courses in Colleges of Education - Jacob Issaka; Hammond, Daniel Kwasi; Nomah, Emmanuel; Fiawoo, Duncan Dodzi (Social Education Research, 2022)
Research plays a critical role in the building of knowledge and the solving of societal problems. This study seeks to assess pre-service teachers for research courses in the Colleges of Education in the Oti Region of Ghana. The study aims to assess pre-service teachers' attitudes towards research courses in the Colleges of Education in the Oti Region of Ghana. The study adopted a quantitative design. The survey research method was, however, used because it helps to collect data on attitudes. Simple random sampling was used to select 200 respondents. The data collection instrument used was a questionnaire. The data were analysed using descriptive and correlational statistical analyses. It was found that pre-service teachers have negative attitudes toward studying research methods and writing research project work. They see both research methods and the writing of research project work as complex and difficult; hence, they have high anxiety about research and dislike the research courses. It was concluded that general attitudes toward studying research methods are directly linked to the perceived challenges of research. It is recommended that the challenges pre-service teachers face in learning research courses should be addressed to improve their attitudes towards research.